2022
DOI: 10.3390/ijerph19042407
|View full text |Cite
|
Sign up to set email alerts
|

Are Gyms a Feasible Setting for Exercise Training Interventions in Patients with Cardiovascular Risk Factors? An Italian 10-Years Cross-Sectional Survey Comparison

Abstract: Background: Exercise training is a known important prevention and treatment modality in patients with cardiovascular (CV) diseases. However, the CV risk factors in gym users have been poorly studied. The aim of this study was to monitor CV risk factors of gym users over 10 years in order to investigate whether gyms are used settings for secondary disease prevention. Methods: In 2007 and 2017, a cross-sectional research survey was adopted to determine CV risk factors and habits in gym users (18–69 years) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It has been previously described that the increase in the post-exercise expression of FNDC5 is higher (>30%) in active subjects compared with their sedentary counterparts or with patients affected by chronic diseases [35]. It can be deduced that patients with T2D, following physical exercise, can obtain a lower increase in irisin secretion than healthy sub-jects but it is probably still relevant for the improvement of their health status [36]. On the other hand, other studies have shown how the beneficial effect of physical exercise on irisin levels is limited only to populations with certain characteristics, including the presence of metabolic diseases [4].…”
Section: Exercise Training Effect On Irisin Secretion In T2d Patients...mentioning
confidence: 99%
“…It has been previously described that the increase in the post-exercise expression of FNDC5 is higher (>30%) in active subjects compared with their sedentary counterparts or with patients affected by chronic diseases [35]. It can be deduced that patients with T2D, following physical exercise, can obtain a lower increase in irisin secretion than healthy sub-jects but it is probably still relevant for the improvement of their health status [36]. On the other hand, other studies have shown how the beneficial effect of physical exercise on irisin levels is limited only to populations with certain characteristics, including the presence of metabolic diseases [4].…”
Section: Exercise Training Effect On Irisin Secretion In T2d Patients...mentioning
confidence: 99%
“…SFMA was also used to prescribe a tailored exercise program, after evaluating patients' mobility and stability complaints [35]. This is an interesting aspect to be considered in the field of sport medicine, when prescribing a customized physical activity in patients [36] to be performed in specific medical gyms [37]. A recent study proposes the Arm Care Screen (ACS) as a new tool based on the concepts of the SFMA in high school coaches and investigated intra-rater and inter-rater reliability when administered by high school baseball coaches in a sample of baseball players.…”
Section: Discussionmentioning
confidence: 99%
“…During the SARS-CoV-2 pandemic, these inter-regional differences became even more pronounced: in 2020, the physically inactive population was 21.3% and 49.3% in the Veneto region and in Southern Italy, respectively. Therefore, it seems reasonable that the economic burden of PI and the potential cost-savings of the PA interventions throughout Italy may be even greater than in the investigated region alone [ 30 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in terms of the prevention and treatment of many chronic conditions, a tailored exercise prescription and programs, based on specific guidelines, are necessary, although still underutilised [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In order to improve this practice, awareness and knowledge must also be increased, particularly for policy makers.…”
Section: Introductionmentioning
confidence: 99%